Confronting Heidegger a critical dialogue on politics and philosophy - Fried, Gegory, 1961- (New Heidegger research., 2020)
"The question of the relation of Martin Heidegger's thought to politics has been a subject of controversy since the 1930s, when he became an advocate of the National Socialist regime in Germany. This volume addresses this question in a unique format, as a dialogue among leading Heidegger scholars. That dialogue begins with an exchange between Gregory Fried and Emmanuel Faye about Faye's contention that Heidegger's work represents nothing short of "the introduction of Nazism into philosophy." At stake are issues such as what Heidegger himself understood Nazism to be, whether a thinker's life and actions define the meaning of his work, the enduring threat of fascism, and the nature of rationality and philosophy itself. Richard Polt, Matthew Sharpe, Dieter Thoma, William Altman, and Sidonie Kellerer join the conversation, with responses from Fried and Faye."--